2022
DOI: 10.3390/ijms23042028
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tim-3/Gal-9 Axis with NLRC4 Inflammasome in Glioma Malignancy: Tim-3/Gal-9 Induce the NLRC4 Inflammasome

Abstract: Tim-3/Gal-9 and the NLRC4 inflammasome contribute to glioma progression. However, the underlying mechanisms involved are unclear. Here, we observed that Tim-3/Gal-9 expression increased with glioma malignancy and found that Tim-3/Gal-9 regulate NLRC4 inflammasome formation and activation. Tim-3/Gal-9 and NLRC4 inflammasome-related molecule expression levels increased with WHO glioma grade, and this association was correlated with low survival. We investigated NLRC4 inflammasome formation by genetically regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Additionally, our previous study revealed that the binding of T cell immunoglobulin and the mucin-domain containing-3 (Tim-3), a representative immune checkpoint molecule in glioma, and its ligand, gal-9, induces the NLRC4 inflammasome [ 53 ]. Tim-3/gal-9 showed a positive correlation with NLRC4 and caspase-1, and their expression increased with glioma grade and was associated with poor survival in patients with glioma [ 53 ]. The inflammasome is also associated with T cell-related immune responses and can affect the inflammatory tumor microenvironment in various ways, and its control can be used for the treatment of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our previous study revealed that the binding of T cell immunoglobulin and the mucin-domain containing-3 (Tim-3), a representative immune checkpoint molecule in glioma, and its ligand, gal-9, induces the NLRC4 inflammasome [ 53 ]. Tim-3/gal-9 showed a positive correlation with NLRC4 and caspase-1, and their expression increased with glioma grade and was associated with poor survival in patients with glioma [ 53 ]. The inflammasome is also associated with T cell-related immune responses and can affect the inflammatory tumor microenvironment in various ways, and its control can be used for the treatment of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…As the inflammatory microenvironment and immune escape are hallmarks of glioma progression, in many tumors, these mechanisms are interrelated and cooperate in the malignant transformation of cancer [ 55 – 57 ]. During glioma progression, tumor cells modulate the expression profile of immune checkpoint molecules and their ligands [ 58 ]. TIM-3 receptor modulates microglia function and regulates the interaction of microglia with nerve cells [ 59 ].…”
Section: Tim-3 In Neoplasmsmentioning
confidence: 99%
“…The binding between Tim-3 and Gal-9 promotes tumor growth and suppresses the adaptive immune system [ 62 ]. A study by Simet al found that the Tim-3/Gal-9 axis association with the NLRC4 inflammasome contributes to glioma development [ 58 ]. Tim-3/Gal-9 regulation was positively correlated with NLRC4 inflammasome, NLRC4, and caspase-1 expression.…”
Section: Tim-3 In Neoplasmsmentioning
confidence: 99%